NavWear: design and evaluation of a wearable device for obstacle detection for blind and visually impaired people - dos Santos, Aline Darc Piculo (2025)
Purpose: Wearable devices have been developed to improve the outdoor mobility of blind and visually impaired (BVI) people. While the functionality of these solutions has been widely evaluated, research on user-device interaction remains scarce. This study describes the development and evaluation of the Navigation Wearable System (NavWear), a wearable device for obstacle detection to assist the outdoor mobility of BVI people. Materials and Methods: The system is based on an RGB-D camera and haptic feedback, integrated into a backpack developed to improve usability and user interaction. Ten blindfolded participants were recruited to evaluate the prototype and completed obstacle courses in three conditions: (i) NavWear; (ii) white cane, and (iii) both devices combined to compare their performance and perceived usability. Results and Conclusions: The results indicate that using the NavWear with the white cane resulted in fewer obstacle collisions, less frustration, and a higher perception of safety. These findings suggest that the prototype can potentially assist the outdoor mobility of BVI people. The results also provide new insights into improving the prototype, including contributions to the design of assistive technology devices that can lead to the engaged use of these devices.